2021
DOI: 10.4491/eer.2021.006
|View full text |Cite
|
Sign up to set email alerts
|

Feature analysis on air quality in the main urban area of Nanchong City in 2015–2018

Abstract: This study evaluates the air quality in Nanchong City in 2015–2018 based on automatic monitoring data and meteorological data in the main urban area. Results show that overall air quality in the main urban area of Nanchong was standard and improved from 2015 to 2018. SO2, NO2, and CO had slight influences on air quality in the study area, whereas excessive annual average PM2.5 and increasing O3 concentration challenged the air quality. The monthly average mass concentrations of particulate matters (PM2.5 and P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 39 publications
0
1
0
Order By: Relevance
“…Basin and affected the PM concentration of Nanchong at times [33]. Because dust particles are mainly composed of larger particles, the concentrations of PM 10 and PM 2.5 in the air rise simultaneously in dusty weather, but the increase in the range of PM 10 is much higher than that of PM 2.5 , resulting in a significant decline in the PM 2.5 /PM 10 ratio.…”
Section: Characteristic Of Pm 25mentioning
confidence: 99%
See 2 more Smart Citations
“…Basin and affected the PM concentration of Nanchong at times [33]. Because dust particles are mainly composed of larger particles, the concentrations of PM 10 and PM 2.5 in the air rise simultaneously in dusty weather, but the increase in the range of PM 10 is much higher than that of PM 2.5 , resulting in a significant decline in the PM 2.5 /PM 10 ratio.…”
Section: Characteristic Of Pm 25mentioning
confidence: 99%
“…It can be concluded that PM 2.5 pollution in Nanchong was relatively severe during the study period. Lei et al [33] found that PM 2.5 was the main non-attainment pollutant in the urban areas of Nanchong City from 2015 to 2018, and the annual average concentrations of PM 2.5 exceeded 35 μg /m 3 for four consecutive years. Similarly, the other cities in the Sichuan Basin also showed severe PM 2.5 pollution between 2009 and 2016 [14,[34][35].…”
Section: Characteristic Of Pm 25mentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to cyclones or anticyclones, the transit of a cold front indirectly contributed to the increase in the particulate matter (PM) concentration in Shijiazhuang via the long-transported upper airflow [23]. Furthermore, the relationship between PM concentrations and wind speed in dust pollution was also investigated [24].…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, with the continuous occurrence of haze in major cities in China [1][2], air quality has become increasingly worse. More and more attention has been paid to the harm caused by fine particles, with the emission of vehicle exhaust being of the main sources of pollution [3][4][5].…”
Section: Introductionmentioning
confidence: 99%